Management of hypertension in pregnancy. Issue 5 (October 2020) - Amro, Farah; Sibai, Baha
Abstract: Hypertensive diseases of pregnancy remain a leading cause of maternal and neonatal morbidity and mortality. Therefore, we sought to review the management of these conditions in pregnancy. In this review we discuss the most updated definitions, different antihypertensives, delivery recommendations and overall goals of management, including their effects on uteroplacental perfusion. We also highlight different medical situations where one antihypertensive may be preferable over others.